Identification of Various Fishing Activities and the Outpouring of Time of Women Fishermen in Cilacap Regency, Indonesia - Agnes Puspitasari Sudarmo; Yogi Putranto (International Journal of Business, Economics, and Social Development, 2021)
Fishing women have unique roles and dual roles not only as housewives but also as economic backbones. Women fishermen help their husbands work to be able to meet the needs of the family. The purpose of this research is to identify the variety of fishing activities and the outpouring of time of women fishermen in Cilacap Regency. The location of this research is at the Fish Auction Place (TPI) TPI Tegal Katilayu, TPI Menganti Kisik, and TPI Lengkong. Descriptive methods based on case studies were used in this study. The sampling method used was purposive sampling, and the number of samples taken by 55 women fishermen. The results showed that the variety of activities carried out by women fishermen were also dominated by economic activities in addition to their roles as a housewife.